Syndesmotic fixation in unstable ankle fractures: Does early post-operative weight bearing affect radiographic outcomes?. Issue 3 (March 2019) - Al-Hourani, K.; Stoddart, M.; Chesser, T.J.S.
Highlights: Early full weight bearing post-syndesmotic fixation was not associated with early radiographic diastasis at 6 weeks. Early full weight bearing post-syndesmotic fixation was not associated with late radiographic diastasis at 12 weeks. There was no association between immobilization in boot or cast and post-operative diastasis. There is no association with weight bearing status and negative secondary post-operative outcomes. Abstract: Objective: To analyse whether early post-operative full weight bearing following syndesmotic ankle fixation affected radiographic outcomes suggestive of diastasis. Design: Retrospective comparative cohort study over a two year period. Setting: Level 1 trauma centre Patients/Participants: 152 consecutive patients sustaining an unstable ankle fracture requiring syndesmotic stabilisation were included. Exclusions were 49 patients who had trimalleolar fixation without syndesmosis screws, one patient who had concomitant ankle and talar fracture. Five patients were lost to follow up and eleven patients were followed up in other centres. A total of 86 patients were analysed Intervention: Protected or full weight bearing. Main Outcome Measurement: The primary outcome measure was early diastasis. The secondary outcomes were late diastasis, wound complications and re-operation. Analysis of variance was used for the predictor variable of weight bearing status. We assumed a priori that p values of less than 0.05 were significant. Results: Median age was 36 (IQR 30), with 54 males and 32 females. Median follow up was 12 weeks (IQR 6). There was no significant difference when comparing weight bearing status and change in radiographic measurements intra-operatively compared to 6 and 12 week follow up radiographs (tibiofibular clear space p = 0.799, tibiofibular overlap p = 0.733 and medial clear space p = 0.261). Conclusion: After surgical stabilization of an unstable syndesmotic injury, full weight bearing did not lead to syndesmotic diastasis in the early post-operative period. Full weight bearing is recommended following ankle fixation which includes syndesmotic fixation.